Gyejibongneyong-hwan, a herbal medicine for the treatment of dysmenorrhoea with uterine fibroids: a protocol for a randomised controlled trial. Issue 11 (24th November 2016) - Jung, Jeeyoun; Lee, Ju Ah; Ko, Mi Mi; You, Sooseong; Lee, Eunhee; Choi, Jiae; Kang, Byoung-Kab; Lee, Myeong Soo
Abstract : Introduction: Gyejibongneyong-hwan (GBH), or the Guizhi Fuling Formula in Chinese, is widely used to treat uterine fibroids in East Asian countries including Korea, China and Japan. This study will assess the efficacy and safety of the GBH formula for the treatment of dysmenorrhoea. Methods and analysis: This study will be a randomised double-blind controlled trial with two parallel arms: the GBH group and the placebo group. This trial will recruit 38 women between 18 and 45 years of age with secondary dysmenorrhoea with uterine fibroids. The investigational drugs, either GBH or placebo, will be administered to the participants three times per day for two menstrual periods (8 weeks). The participants will be followed up for three menstrual cycles after administration of the drugs. The primary outcome will be the Numeric Rating Scale score of average menstrual pain. All analyses will be performed with SAS (V.9.1.3; SAS Institute, Cary, North Carolina, USA) by a statistician blinded to the allocation of the groups. Statistical analysis will be undertaken on the intent-to-treat (ITT) basis with a 95% CI using the last observation carried forward for missing values. The ITT analysis will include all randomised patients. Ethics and dissemination: This research protocol has been reviewed and approved by the institutional review boards of the trial centre (number WSOH IRB 1606-03). Written informed consent will be obtained from all study participants prior to enrolment in the study. The results will be published in a peer-reviewed journal and will be disseminated electronically and in print. Trial registration number: KCT0001967.